2015
DOI: 10.1371/journal.pone.0143726
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Fluid Resuscitation Rate with and without External Pressure Using Two Intraosseous Infusion Systems for Adult Emergencies, the CITRIN (Comparison of InTRaosseous infusion systems in emergency medicINe)-Study

Abstract: IntroductionIntraosseous infusion is recommended if peripheral venous access fails for cardiopulmonary resuscitation or other medical emergencies. The aim of this study, using body donors, was to compare a semi-automatic (EZ-IO®) device at two insertion sites and a sternal intraosseous infusion device (FASTR™).MethodsTwenty-seven medical students being inexperienced first-time users were randomized into three groups using EZ-IO and FASTR. The following data were evaluated: attempts required for successful plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…Despite the fact the cavity is empty after saline flush, bone spicules increase flow resistance between bone cavity and vascular system. Therefore, use of pressure bags is absolutely required to enhance flow rates [ 15 ] and enable medications to reach the vascular system. When this recommendation is implemented, the IO access allows rapid delivery of large amounts of fluids and medications in emergency situations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Despite the fact the cavity is empty after saline flush, bone spicules increase flow resistance between bone cavity and vascular system. Therefore, use of pressure bags is absolutely required to enhance flow rates [ 15 ] and enable medications to reach the vascular system. When this recommendation is implemented, the IO access allows rapid delivery of large amounts of fluids and medications in emergency situations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This finding is not surprising as prior studies of blood, crystalloid, and hetastarch infusions noted higher flow rates with increasing infusion pressures. 23,34,35,[40][41][42] Previous research has also noted pressure bag flow rates to be superior to the rapid infuser. 23,43 The difference between PB and rapid infuser in both studies was related primarily to interruption in infusion from frequent overpressure alarms.…”
Section: Discussionmentioning
confidence: 99%
“…Human, cadaver, and animal research has consistently shown pressurized IO infusion rates are superior to gravity flow rates. 34,40,44 The gravity transfusion arm was removed from this present study after noting futile flow rates during the pilot phase. 23 On the surface, pilot data may appear to be in conflict with a recent research on IO blood transfusion via gravity, in which flow rates were reported at 50 mL/min in the human sternum.…”
Section: Discussionmentioning
confidence: 99%
“…Intraosseous injection provides entry for resuscitation drugs and fluid resuscitation [12][13][14]. However, flow through the IO catheter must be initiated by an initial flush of at least 10 mL of saline and maintained with the use of a pressure infusion bag inflated at 300 mmHg in accordance with the instructions of use [15].…”
Section: Discussionmentioning
confidence: 99%